In‐hospital management of persons with haemophilia and COVID‐19: Practical guidance. Issue 5 (29th July 2020) - Hermans, Cedric; Lambert, Catherine; Sogorb, Amaury; Wittebole, Xavier; Belkhir, Leila; Yombi, Jean Cyr
Abstract: A new disease (COVID‐19) caused by a coronavirus (SARS‐CoV‐2) that appeared in China at the end of 2019 is currently spreading globally. This emerging virus is mainly responsible for respiratory tract infections and potentially fatal pneumonia, mainly in more frail patients. Persons with haemophilia of variable severity and from all parts of the world will likely be infected and develop COVID‐19. We here propose practical guidance for the in‐hospital specific management of haemophilia persons with COVID‐19 including their possible transfer to the intensive care unit. Rapid identification of the haemophilia status, undelayed and regular liaison with the haemophilia team, proper therapy with factor concentrates or alternative treatments appear instrumental to prevent haemophilia‐related complications in this setting. Information of patients and their families about COVID‐19, psychological support and good appreciation of the impact of haemophilia on therapeutic decisions including end‐of‐life directives are also addressed.